Comparison between Two Doses of Suprachoroidal Triamcinolone Acetonide among Cases of Resistant Diabetic Macular Edema: Doi: 10.36351/pjo.v40i2.1756 - Muhammad Zunair Aziz; Kazi, Umar; Ali Zia; Nasir Memon; Abdul Qadeem (Pakistan Journal of Ophthalmology, 2024)
Purpose: To compare the effectiveness and safety of two doses of supra-choroidal Triamcinolone Acetonide (TA)in patients of resistant diabetic macular edema. Study Design: Quasi experimental study. Place and Duration of Study: Al-Ibrahim Eye Hospital, Karachi, from April 2023 to September 2023. Methods: Thirty-two cases of resistant diabetic macular edema were selected using a convenient sampling technique and divided into two groups. Group A received a single suprachoroidal injection of TA at a concentration of 2 mg/0.1 ml, while Group B received the same drug via the same route at a concentration of 4 mg/0.1 ml. All cases were monitored for any serious adverse effects the following day. Follow-up checkups were conducted for all cases at 1, 3, and 6 months. Results: Mean age of patients for group A and B was 56.24±1.2and 56.33±2.6years respectively. Both the groups were equivalent in all ophthalmological measurements best corrected visual acuity, central macular thickness and intraocular pressure (BCVA, CMT, IOP) at baseline checkups. At 6thmonth follow up, both groups showed improved BCVA and decreased CMT compared to baseline, but group B had a significant increase in IOP (p = 0.001). Additionally, cataract progression was slower in group A. Conclusion: Both doses of suprachoroidal TA are equally effective in cases of resistant diabetic macular edema in terms of improved BCVA and reduced CMT. However, the lower dose (2mg/0.1 ml) showed advantages in terms of fewer complications, specifically less likelihood of raised intraocular pressure and cataract formation.